Monitoring System and Automatic Drug Administration in Betta Fish Farming Ponds - Pratama, Nasrul Deva; Rakhmania, Amalia Eka; Dali, Sri Wahyuni (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
This research focuses on a website based monitoring system for pH, temperature, turbidity, and water level in a betta fish pond, including the administration of pH and salt medication, as well as automatic water draining and refilling when the pond water becomes cloudy. The results show a high level of accuracy. pH measurements using five samples with values of 5.65, 6.36, 7.32, 8.21, and 9.47 achieved an accuracy of 99.48 percent. Ultrasonic distance measurements using five samples with distances of 5 centimeter, 6 centimeter, 7 centimeter, 8 centimeter, and 9 centimeter achieved an accuracy of 100 percent. Temperature measurements using five samples with values of 25 degree Celsius, 26.42 degree Celsius, 27.90 degree Celsius, 28.50 degree Celsius, and 29.30 degree Celsius achieved an accuracy of 99.47 percent. Water level measurements using five samples with heights of 1.5 centimeter, 2 centimeter, 2.5 centimeter, 3 centimeter, and 3.5 centimeter achieved an accuracy of 100 percent. In addition, the developed website successfully displays real time data from each sensor reading and allows users to set threshold limits for each sensor parameter